Characterizing Flow and Structure of Diabetic Retinal Neovascularization after Intravitreal Anti-VEGF Using Optical Coherence Tomography Angiography: A Pilot Study - Christof Haensli; Katrin Fasler; Daniel Barthelmes; Sandrine A. Zweifel (Journal of Ophthalmology)
Background/Aims. This study evaluates changes of flow and structure of diabetic retinal neovascularization (NV) treated with intravitreal antivascular endothelial growth factor (VEGF) agents using optical coherence tomography angiography (OCTA). With OCTA, retinal blood vessels are visualized at high resolution to separately look at flow and structure information without the need for dye injection. We introduce a new measurement method including and combining information of flow and structure. Methods. Retrospective observational case series. Patients with proliferative diabetic retinopathy (PDR) were treated with intravitreal antiVEGF injections. Retinal NV were repeatedly imaged using swept-source OCTA (Zeiss PlexElite 9000) at baseline, after initial treatment block with 3-4 monthly injections, and during a follow-up period of up to 51 weeks. Change of size and flow density of the structural and angio area of NV was assessed. Results. Nine NV in eight eyes of five patients were analyzed with a median follow-up time of 45 weeks. After the initial treatment block, en face structural area regressed, 18.7% ± 39.0% (95% CI 44.2–6.8%, p=0.26), and en face angio area regressed, 51.9% ± 29.5% (95% CI 32.6 to 71.2%, p=0.007). Flow density within the en face structural area decreased by 33% ± 19.2% (95% CI 20.5–45.5%, p=0.0077). Flow density within the en face angio area decreased by mean 17.9% ± 25.2% (95% CI 1.4–34.4%, p=0.066). In two fellow eyes, NV recurrence could be observed before the onset of vitreous bleeding in one. Conclusion. Our study introduces a new quantitative measurement for NV in PDR, combining structure and flow measurement. The structure area remained after treatment, while its flow density and angio area regressed. We propose this measurement method as a more physiological and possibly more comparable metrics.